Knowledge, attitudes, and practices of gastric cancer patients toward nutritional therapy - Yu, Hui; Li, Ling; Gu, Jing; Wang, Jing; Su, Hui; Lu, Hui; Zhou, Yuqing; Xia, Jingfang; Xu, Yongping; Liang, Danhua; Yang, Yuling; Chen, Ying (Frontiers in Medicine, 2025)
BackgroundTo investigate the knowledge, attitude, and practice (KAP) of patients with gastric cancer (GC) toward nutritional therapy.MethodsThis cross-sectional study was conducted from January to March 2024 at the Affiliated Hospital of Jiangnan University (Wuxi, China) and enrolled patients with GC. Questionnaires (Cronbach’s α = 0.923) were used to collect data on demographics and KAP dimensions. Scores >75% were considered good. Multivariable analyses were performed to examine the factors associated with KAP. A structural equation modeling (SEM) analysis was performed to examine the relationships among KAP dimensions.ResultsThe analysis included 486 valid questionnaires. The median knowledge, attitude, and practice scores were 6.0 (0–16; 37.5%), 26.0 (7–35; 74.3%), and 28.7 (8–40; 71.7%) indicating poor KAP. Only agricultural, forestry, animal husbandry, fishery, and water conservancy production personnel (OR = 0.09, 95%CI: 0.02–0.49, p = 0.006) were independently associated with knowledge. Knowledge (OR = 1.11, 95%CI: 1.05–1.18, p < 0.001) and a monthly income of 10,000–20,000 (OR = 3.85, 95%CI: 1.23–12.06, p = 0.021) were independently associated with attitude. Knowledge (OR = 1.22, 95%CI: 1.15–1.30, p < 0.001), attitude (OR = 1.21, 95%CI: 1.11–1.32, p < 0.001), personnel other than leading cadres of state organs and enterprises (all OR < 1 and all p < 0.05), and a monthly income of 10,000–20,000 yuan (OR = 3.02, 95%CI: 1.15–7.96, p = 0.025) were independently associated with practice. Knowledge had a direct positive influence on attitude (β = 0.350, p < 0.001) and practice (β = 0.460, p < 0.001) and an indirect positive influence on practice (β = 0.146, p < 0.001). Attitude had a direct positive influence on practice (β = 0.417, p < 0.001).ConclusionPatients with GC in Wuxi partly had poor KAP toward nutritional support.